Differences in spatiotemporal pressure and performance between Chinese and German elite youth football players during matches - Liang, Yapu; Li, Tianhe; Xu, Hansi; Zhang, Peng (Frontiers in Psychology, 2025)
IntroductionIn modern football, spatial and temporal pressure significantly influence player performance and tactical outcomes, particularly in youth competitions. This study aims to investigate the spatial pressure differences between Chinese and German U17 elite youth football teams, focusing on the ball-handler’s distance to the nearest defender (D).MethodsVideo analysis was conducted to measure D across various match contexts, including scorelines (leading, tied, and trailing), game phases (passing and receiving), pass outcomes (successful and unsuccessful), and pitch zones. Statistical analyses were performed using non-parametric methods to compare the D under different conditions. The Mann–Whitney U test and Kruskal–Wallis H test were used to identify significant differences, with post hoc comparisons conducted where necessary.ResultsResults show that the German team consistently maintained greater D than the Chinese team (p < 0.001, d = 0.463), highlighting their superior spatial management and tactical adaptability.DiscussionGreater D was associated with enhanced offensive flexibility and defensive stability, allowing the German team to create space effectively and maintain structural integrity under pressure. In contrast, the Chinese team’s smaller D suggested limitations in spatial utilization and higher defensive engagement risks. These findings underscore the importance of tactical training emphasizing spatial awareness and balanced pressure management, providing valuable insights for youth football development.